Smarter is greener: can intelligent manufacturing improve enterprises’ ESG performance? - Gao, Da; Tan, Linfang; Chen, Yue (Humanities & social sciences communications, 2025)
Environmental, Social, and Governance (ESG) is highly consistent with the “Dual Carbon” goals proposed by China and has become an important indicator to measure enterprises’ high-quality development. This study explores the impact of intelligent manufacturing on corporate ESG performance and its potential mechanisms. Using the dataset of China’s A-share listed companies from 2009 to 2021, we treat the intelligent manufacturing pilot programs (IMPP) as a quasi-natural experiment and use the staggered difference-in-difference model for empirical analysis. The results show that corporate ESG performance is significantly improved after participating in IMPP, and the placebo and entropy balancing tests further reconfirm the results. The mechanism analysis shows that IMPP works in two main ways: promoting enterprises’ green innovation and reducing the misallocation of financial resources. The heterogeneity analysis shows that the IMPP significantly improves the ESG performance of Non-state-owned, high-tech, and heavy-polluting enterprises. In addition, the IMPP improves the enterprises’ green total factor productivity and brings significant economic benefits. This study has far-reaching policy implications for promoting the quality-driven development of China’s manufacturing industry and the sustainable development of enterprises.